EFEKTIVITAS PEMBELAJARAN DARING BERBASIS EDMODO TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA - Muhammad Syahril Harahap; Rahmatika Elindra; Anggi Anggraini Nasution (SIGMA: JURNAL PENDIDIKAN MATEMATIKA, 2022)
The purpose of this study was to describe the effectiveness of the application of Edmodo-based online learning on the Ability to Understand Mathematical Concepts (AUMC) of students in class VII-1 of SMP Negeri 4 Padangsidimpuan. This research uses descriptive quantitative method with a sample of 15 students.Data collection techniques in this study using observation and tests. Based on the results of the descriptive analysis, it was found: (a) The average application of Edmodo-based online learning was 3.2 with the "Very Good" category, (b) The average student critique before the application of Edmodo-based online learning was 68 with the "Enough" category. and after the implementation of Edmodo-based online learning is 75 with the "Good" category.Furthermore, based on inferential statistics using the t test (paired sample test) and the N-Gain formula, the results obtained show a significant value of less than 0.05 (0.000 0.05) and g = 0.49 with the "Medium" category. This means that the application of Edmodo-based online learning is effective for the AUMC of students in class VII-1 of SMP Negeri 4 Padangsidimpuan.